2007
DOI: 10.1161/circulationaha.106.682054
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endoplasmic Reticulum Stress in Atherosclerotic Plaques Associated With Acute Coronary Syndrome

Abstract: Background-The endoplasmic reticulum (ER) responds to various stresses by upregulation of ER chaperones, but prolonged ER stress eventually causes apoptosis. Although apoptosis is considered to be essential for the progression and rupture of atherosclerotic plaques, the influence of ER stress and apoptosis on rupture of unstable coronary plaques remains unclear. Methods and Results-Coronary artery segments were obtained at autopsy from 71 patients, and atherectomy specimens were obtained from 40 patients. Smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
283
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(310 citation statements)
references
References 42 publications
16
283
1
2
Order By: Relevance
“…However, if ERS is prolonged or too severe, the UPR may result in the activation of apoptosis [77] . SMCs synthesize most of the inter- [78] . Pedruzzi et al [79] reported that the 7-ketocholesterol (7-Kchol)-activating pathway induced an early triggering of ERS in SMCs, as assessed by transient intracellular Ca 2+ oscillations and IRE-1, JNK, and AP-1 expression.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…However, if ERS is prolonged or too severe, the UPR may result in the activation of apoptosis [77] . SMCs synthesize most of the inter- [78] . Pedruzzi et al [79] reported that the 7-ketocholesterol (7-Kchol)-activating pathway induced an early triggering of ERS in SMCs, as assessed by transient intracellular Ca 2+ oscillations and IRE-1, JNK, and AP-1 expression.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…During atherogenesis, a maladaptive inflammatory response is initiated by the deposition of cholesterol-rich lipoproteins in the subendothelial layer of arterial walls (6). Signs of ER stress are most prominent in the atherosclerosis-prone regions of vascular lesions, such as the branching points of arteries, and typically observed in macrophages-among other immune cells-infiltrating these regions (7,8). Chronic, irremediable ER stress triggers apoptosis in macrophages, contributing to the growth of the necrotic core Significance Endoplasmic reticulum (ER) stress is linked to the development of complex metabolic diseases, including diabetes, obesity, and atherosclerosis.…”
mentioning
confidence: 99%
“…Work over the last decade has pinpointed ER stress as a driving force for atherosclerosis progression (5,(7)(8)(9)(10). For example, inhibiting the apoptotic signaling downstream of ER stress through genetic deletion of the proapoptotic transcription factor CCAAT box binding enhancer homologous protein (CHOP) or the signal transducer c-jun N-terminal kinase (JNK) blocks atherosclerosis progression (5,(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 In advanced atherosclerotic plaques, the presence of oxidized lipids, inflammation, and metabolic stress induces ER stress and activates UPR. 8 ER stress is also related to cardiac damage and vascular endothelial dysfunction in angiotensin II (Ang II)-induced hypertension. 9 Whether ER stress and UPR are causal to defects of cardiovascular phenotypes under the disease conditions, however, are not fully understood.…”
mentioning
confidence: 99%